Measures of obligation - David Blockley (Cogent Business & Management, 2022)
Principled capitalism has been proposed as a replacement for liberal capitalism. Moral principles should be driving our individual and collective decisions rather than utility and profit. A new unit called an oblig is suggested as a measure of the amount of the substance of the "stuff" that moves around in a social field of obligation forces. The notion of dynamic equilibrium is amplified and obligs are compared with the utils of utility theory and qualitative deposits in "emotional bank accounts". It is concluded that the methods of utility theory are not appropriate for principled capitalism. A new unit of obligatory force is defined as a carson after the ecologist Rachel Carson. It is that force required to change the rate of change of a measured item within an obligation. The mathematics of obligs is developed and illustrated with four examples, two concerning individual relationships and two as applied to company and national government accounts.
Keywords: A11; C02; C18; E60; E66; E70; 650; Capitalism; emotional bank account; measures; obligations; utility theory